Characteristics of Pore Structure in Coal from the Chengzhuang Mining Area - Chen, Yilong (International Journal of Natural Resources and Environmental Studies, 2026)
To investigate the pore structure characteristics and multi-scale distribution of coal in the Chengzhuang mining area, coal samples from the Shanxi Formation were selected for analysis. High-pressure mercury intrusion (MIP), low-temperature nitrogen adsorption (LTNA), and scanning electron microscopy (SEM) were employed to comprehensively characterize pore types, pore size distribution, and pore-throat structure. The results indicate that the pore system in the study area is mainly composed of metamorphic pores and exogenous pores, with relatively poor connectivity. The MIP results show that the pore volume of both samples is dominated by transitional pores, followed by micropores, while mesopores and macropores account for relatively small proportions, suggesting that the pore system is primarily composed of small- to medium-scale pores. The LTNA results reveal that transitional pores contribute significantly to the pore volume, whereas micropores dominate the specific surface area. This indicates that pore volume is mainly controlled by transitional pores, while the specific surface area is primarily governed by micropores.